Risk management in museums: the importance of fire risk management system / Puteri Sidrotul Nabihah Saarani - Saarani, Puteri Sidrotul Nabihah (2012)
Museum is institution that enables people to explore collections for inspiration, learning and enjoyment. But when it comes to historical museums, not only the collections in it are valuable but the structure of the building also has the value. Throughout the world, it was recorded that 25 museums are damaged and some are destroyed in fire. Unbelievable 5 of them are the local cases and 4 of diem happen in historical museums. Although the number of museums burnt down in fire is considered as small, yet great precautions should always be taken to prevent such incidents from occurring because museums are treasures and peoples’ lives are precious and priceless. Comparative case study approach was employed for this dissertation which included die 9 historical museums in Dalaran Pahalawan Melaka. Personal interviews and observations during visits to the museums were die main methods used to collect data. The study is mainly focus to ways of the selected case study managing the fire risk. By using four basic principles in managing fire risk, die data have been collected and analyzed. From this study conducted, it found that the fire risk management system in the historical museums is still poor. It do apply a few basics fire fighting devises but still in a very small quantity. Therefore few guidelines are suggested to help the management in improving die current practice.